Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together (NHT) Berbantuan Media Kartu Berseri Untuk Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Negeri 2 Sukadana, Kubu, Karangasem - I Ketut Pramana Adi Putra (Jayapangus Press, 2019)
This study aims to determine the improvement of social studies learning outcomes by applying the cooperative learning model numbered heads together (NHT) assisted by serial card media in class V students in second semester Sekolah Dasar Negeri 2 Sukadana 2015/2016 Academic Year. This type of research uses a type of classroom action research. Classroom action research consists of four stages, namely: (1) planning, (2) action, (3) observation / evaluation, and (4) reflection carried out in two cycles with three meetings in each cycle. The subjects of this study were the fifth grade students of Semester II of Sekolah Dasar Negeri 2 Sukadana Academic Year 2015/2016 as many as 25 people consisting of 12 men and 13 female students. Data on student learning outcomes were collected by objective tests combined with stuffing tests and analyzed descriptively quantitatively. The results showed that the application of the NHT type of cooperative learning model with the help of serial card media was able to improve student learning outcomes in social studies subjects in class V Sekolah Dasar Negeri 2 Sukadana. The results showed that the average value obtained in the first cycle was 13.56 and the ability level was 67.80% with the medium category. Classical completeness reached 56% with criteria not yet completed. While in the second cycle the average value was 16.32 and the ability level was 81.60% with a high category. Classical completeness reaches 100% with complete criteria. So, the increase in the average Social Studies learning outcomes from cycle I to cycle II is 2.76 and the increase in the level of ability from cycle I to cycle II is 13.8%. While the increase in classical completeness from cycle I to cycle II is 44%.